2023
DOI: 10.1101/2022.12.29.522275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An engineered ACE2 decoy broadly neutralizes Omicron subvariants and shows therapeutic effect in SARS-CoV-2-infected cynomolgus macaques

Abstract: The Omicron variant continuously evolves under the humoral immune pressure obtained by vaccination and SARS-CoV-2 infection and the resultant Omicron subvariants exhibit further immune evasion and antibody escape. Engineered ACE2 decoy composed of high-affinity ACE2 and IgG1 Fc domain is an alternative modality to neutralize SARS-CoV-2 and we previously reported its broad spectrum and therapeutic potential in rodent models. Here, we show that engineered ACE2 decoy retains the neutralization activity against Om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…The Y489H mutation reduced ACE2 affinity and enabled escape from the ACE2 decoy. But this mutation also increased spike expression and overall infectivity was compensatively preserved (Urano et al, 2023). Similar decoy escape was reported in the case of CD4 decoys against HIV infection and it was suggested that nanoparticle coating CD4 could overcome the escape due to the avidity effect (Hoffmann et al, 2020).…”
Section: Discussionsupporting
confidence: 60%
“…The Y489H mutation reduced ACE2 affinity and enabled escape from the ACE2 decoy. But this mutation also increased spike expression and overall infectivity was compensatively preserved (Urano et al, 2023). Similar decoy escape was reported in the case of CD4 decoys against HIV infection and it was suggested that nanoparticle coating CD4 could overcome the escape due to the avidity effect (Hoffmann et al, 2020).…”
Section: Discussionsupporting
confidence: 60%